2020
DOI: 10.3390/cells9010246
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approaches for Identifying the Molecular Background of Schizophrenia

Abstract: Recent advances in psychiatric genetics have led to the discovery of dozens of genomic loci associated with schizophrenia. However, a gap exists between the detection of genetic associations and understanding the underlying molecular mechanisms. This review describes the basic approaches used in the so-called post-GWAS studies to generate biological interpretation of the existing population genetic data, including both molecular (creation and analysis of knockout animals, exploration of the transcriptional eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 143 publications
0
9
0
Order By: Relevance
“…Notably, gene wide association studies (GWAS) on schizophrenia have failed to show a change in gene sequence at any single nucleotide polymorphism in the muscarinic M1 receptor is associated with a changed srisk for schizophrenia (Schizophrenia Working Group of the Psychiatric Genomics et al, 2014), a replication on what was reported using DNA from postmortem CNS (Scarr et al, 2009). It is proposed that in the post-GWAS error the only studies that will be able to contribute to understanding the complex aetiology of schizophrenia, and that will led to new treatments for the disorder, will be those that translate the GWAS findings into an understandable biology (Golov et al, 2020). However, the advances made in understanding the role of the muscarinic M1 receptor in the aetiology of schizophrenia and as a potential drug target would suggest a fixation on only GWAS related biology is over restrictive.…”
Section: Resultsmentioning
confidence: 96%
“…Notably, gene wide association studies (GWAS) on schizophrenia have failed to show a change in gene sequence at any single nucleotide polymorphism in the muscarinic M1 receptor is associated with a changed srisk for schizophrenia (Schizophrenia Working Group of the Psychiatric Genomics et al, 2014), a replication on what was reported using DNA from postmortem CNS (Scarr et al, 2009). It is proposed that in the post-GWAS error the only studies that will be able to contribute to understanding the complex aetiology of schizophrenia, and that will led to new treatments for the disorder, will be those that translate the GWAS findings into an understandable biology (Golov et al, 2020). However, the advances made in understanding the role of the muscarinic M1 receptor in the aetiology of schizophrenia and as a potential drug target would suggest a fixation on only GWAS related biology is over restrictive.…”
Section: Resultsmentioning
confidence: 96%
“…Another approach to inferring the effector genes of regulatory regions is the analysis of the spatial chromatin organization by C-methods (chromosome conformation capturebased methods), including ChIA-PET, HiChIP (in situ Hi-C followed by ChIP), and promoter capture Hi-C [50,51]. Although the active regulatory regions are thought to be spatially close to the promoters of their target genes, spatial proximity does not guarantee a functional relationship between a regulatory region and a gene [53,54]. Moreover, while an individual TFBS variant may contribute, neighboring risk variants might also modulate the transcriptional landscape of target genes.…”
Section: Challenges Of Investigating Genetic Variants In Tfbssmentioning
confidence: 99%
“…However, high-throughput versions of C-methods, such as Hi-C, allow for the annotation of all target genes for all potential enhancers from GWAS-identified regions in one experiment. These techniques are often used as intermediate steps for the detection of genes potentially regulated by enhancers in GWAS-identified regions before performing time-consuming functional confirmation [54].…”
Section: Challenges Of Investigating Genetic Variants In Tfbssmentioning
confidence: 99%
“…P<0.05) (4)(5)(6). The SCZ-PRS can then be utilized to explore the cumulative impact of genetic risk for the disease over phenotypical dimensions; a more powerful approach than the examination of the effects of single variants (7)(8)(9)(10)(11)(12). The power of the polygenic model of schizophrenia is evidenced by recent studies using SCZ-PRS revealing association with negative symptoms and anxiety (13) and childhood and adolescent psychopathology (14).…”
Section: Introductionmentioning
confidence: 99%